1977
DOI: 10.1530/acta.0.0850791
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Lats Activity in Immunoglobulin G Subclass

Abstract: The immunological character of LATS was examined by affinity chromatography on Anti-IgG, Anti-Fab, Anti-Fc and Staphylococcal Protein A bound Sepharose. By affinity chromatography on Anti-IgG, Anti-Fab and Anti-Fc bound Sepharose, it is possible to separate LATS-immunoglobulin from LATS positive serum without loss of activity. Affinity chromatography on Protein A bound Sepharose is useful for obtaining further purified LATS-immunoglobulin. By this method, it is possible to separate I gG molecules of the subcla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Similar to the results reported by Zakarija (1983) and Ochi et al (1977) we found a heterogeneous distribution of TDA in IgG-subclasses. With one exception displacing activity was maximal or enriched compared with whole IgG in peak III after Protein-A subfractionation corresponding to IgG 1 • Despite considerable contamination with other subclasses peak II (IgG 2 ) was associated with the receptor binding activity only in one case, whose IgG was highly positive for TDA in all fractions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the results reported by Zakarija (1983) and Ochi et al (1977) we found a heterogeneous distribution of TDA in IgG-subclasses. With one exception displacing activity was maximal or enriched compared with whole IgG in peak III after Protein-A subfractionation corresponding to IgG 1 • Despite considerable contamination with other subclasses peak II (IgG 2 ) was associated with the receptor binding activity only in one case, whose IgG was highly positive for TDA in all fractions.…”
Section: Discussionsupporting
confidence: 92%
“…These findings provided evidence that thyroid stimulating antibodies are not distributed at random among IgG molecules. Ochi, Yoshimura, Takashi and Miyazaki (1977) found that LATS-activity was not evenly distributed among IgG-subclasses. To obtain further information on the oligoclonal or even monoclonal character of the antibodies involved, serum from Graves' disease patients was subfractionated, using Protein A bound Sepharose.…”
Section: Introductionmentioning
confidence: 92%
“…Protein A depletion of IgG3 showed that there was no long-acting thyroid stimulator activity in this subclass (19), and pH gradient elution of protein A-bound IgG showed that the major (but not unique) component of TSH receptor binding activity resided in the IgG, plus IgG4 fraction (20). However, further fractionation was not possible using this technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the biological activity in 5 tested samples was equally divided between IgG (l) and IgG (k), and was also found in both Fab (k) and Fab (l) fragments. These facts suggest that TSAb-IgG in the tested cases may be polyclonal, with restricted heterogeneity (IgG 1 subclass restriction has been reported (Ochi et al, 1977)).…”
Section: Discussionmentioning
confidence: 65%